Pengaruh Metode SQ3R Terhadap Penguasan Kosa Kata Bahasa Arab - Hana Azharunnailah; Rinaldi Supriadi; Nunung Nursyamsiah (An Naba, 2023)
ABSTRACT SQ3R is a learning method consisting of: Survey, Question, Read, Recite, and Review. SQ3R is often used to help students' reading skills. Mastering language vocabulary is the main capital to achieve aspects of language skills which include listening, reading, writing, and speaking skills students need to master the vocabulary of the language learned. The research that will be carried out at MTS Al-Inayah in class VIII aims to find out: the influence of SQ3R in mastering Arabic vocabulary in grade VIII students of MTS Al-Inayah Bandung and the difference in student learning outcomes between the application of the SQ3R method and those who do not use SQ3R. This study used an experimental method with a quasi-experimental design. By using the Non-Equivalent Control Group Design scheme. In this design is divided into two, namely the control class and the experimental class is selected without going through randomly. Data collection using test and non-test. The test includes a pre-test and post-test to determine the level of Arabic vocabulary mastery. For non-test data collection using observation and documentation. The results of this study were (1) the SQ3R learning method had an impact on the Arabic language vocabulary mastery of Grade VIII students of MTS Al-Inayah with an increase of 28.85 from an average of 52.30 to 81.15. This is associated with a significance value of 0.00 which is less than the value of 0.05 which means there are differences in the learning outcomes of the experimental class using SQ3R.